1991
DOI: 10.1007/bf02990465
|View full text |Cite
|
Sign up to set email alerts
|

Dietary calcium and blood lead levels in women

Abstract: Nutritional factors are known to influence metabolism and toxicity of several metals in animal experiments, but relevant human data are scarce and inconclusive. In this work, we tested the hypothesis that dietary calcium influences lead metabolism in humans. Blood lead concentrations were used as indicators of lead exposure and metabolism. Two groups of peasant women living in similar conditions in two different regions in Yugoslavia (100 in each) were chosen as subjects for this purpose. In region A, the diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0
2

Year Published

1995
1995
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 13 publications
3
10
0
2
Order By: Relevance
“…These findings are consistent with results from carefully conducted cross-sectional studies finding higher calcium intakes related to lower lead levels (Cifuentes et al 2000;Farias et al 1996;Goyer 1997;Han et al 2000;Hernandez-Avila et al 1996;HertzPicciotto et al 2000;Kostial et al 1991;Miller et al 1990). In a longitudinal study of mother-neonate lead levels in Mexico (Rothenberg et al 1996), greater maternal milk consumption during pregnancy was associated with lower neonatal lead.…”
Section: Discussionsupporting
confidence: 87%
“…These findings are consistent with results from carefully conducted cross-sectional studies finding higher calcium intakes related to lower lead levels (Cifuentes et al 2000;Farias et al 1996;Goyer 1997;Han et al 2000;Hernandez-Avila et al 1996;HertzPicciotto et al 2000;Kostial et al 1991;Miller et al 1990). In a longitudinal study of mother-neonate lead levels in Mexico (Rothenberg et al 1996), greater maternal milk consumption during pregnancy was associated with lower neonatal lead.…”
Section: Discussionsupporting
confidence: 87%
“…Not many epidemiological data on the relationship between dietary calcium intake and the blood lead level in normal population groups are available. Kostial et al recommended adequate calcium (940 mg/d) especially for pregnant and lactating women (to prevent bone resorption) and for children (to enhance bone mass formation) 89) . Further work in this area will be useful particularly in view of a few recent reports in which it has been reported that coprophagy may be a serious complication in the rat model system as both calcium and lead may be recycled 90) .…”
Section: Calciummentioning
confidence: 99%
“…The results of combined treatments with CaNa 2 EDTA and the two thiols (DMPS and MiADMSA) were the more impressive, both in terms of recovery in altered biochemical variables (oxidative stress) and reduction of the body lead burden 50) . There have been recent debates about introducing a combined treatment therapy for lead poisoning 22,88,89) .The two arguments proposed for promoting this treatment point to the fact that (i) The inefficiency of EDTA to decrease brain lead and the ability of thiol chelators like DMSA for their reported role in promoting soft tissue lead mobilization including the brain (ii) addition of MiADMSA to EDTA caused not only higher lead elimination but also better recovery in altered biochemical variables. The studies done by us thus represent a systematic approach to the development of a new therapeutic protocol for the treatment of lead intoxication.…”
Section: Combined Administration Of Two Chelating Agentsmentioning
confidence: 99%
“…A concentração média de chumbo no sangue de camponesas suplementadas com 940mg Ca foi significativamente menor do que o nível médio deste metal encontrado no sangue das mulheres que ingeriram metade deste teor, sugerindo que a ingestão adequada de cálcio pode ser uma das medidas preventivas para a redução da absorção do chumbo (Kostial et al, 1991). Sargent e colaboradores (1999) perceberam que um efeito significativo da suplementação de cálcio nas fórmulas infantis sobre a concentração de chumbo no sangue aconteceu somente nos 4 primeiros meses do acompanhamento.…”
Section: Absorçãounclassified